Improving health care quality and safety: the role of collective learning - Singer SJ; Benzer JK; Hamdan SU (Dove Medical Press, 2015)
Sara J Singer,1–4 Justin K Benzer,4–6 Sami U Hamdan4,6 1Department of Health Policy and Management, Harvard T.H. Chan School of Public Health, Boston, MA, USA; 2Department of Medicine, Harvard Medical School, Boston, MA, USA; 3Mongan Institute for Health Policy, Massachusetts General Hospital, Boston, MA, USA; 4Center for Healthcare Organization and Implementation Research, VA Boston Healthcare System, Boston, MA, USA; 5VISN 17 Center of Excellence for Research on Returning War Veterans, Waco, TX, USA; 6Department of Health Policy and Management, Boston University School of Public Health, Boston, MA, USA Abstract: Despite decades of effort to improve quality and safety in health care, this goal feels increasingly elusive. Successful examples of improvement are infrequently replicated. This scoping review synthesizes 76 empirical or conceptual studies (out of 1208 originally screened) addressing learning in quality or safety improvement, that were published in selected health care and management journals between January 2000 and December 2014 to deepen understanding of the role that collective learning plays in quality and safety improvement. We categorize learning activities using a theoretical model that shows how leadership and environmental factors support collective learning processes and practices, and in turn team and organizational improvement outcomes. By focusing on quality and safety improvement, our review elaborates the premise of learning theory that leadership, environment, and processes combine to create conditions that promote learning. Specifically, we found that learning for quality and safety improvement includes experimentation (including deliberate experimentation, improvisation, learning from failures, exploration, and exploitation), internal and external knowledge acquisition, performance monitoring and comparison, and training. Supportive learning environments are characterized by team characteristics like psychological safety, appreciation of differences, openness to new ideas social motivation, and team autonomy; team contextual factors including learning resources like time for reflection, access to knowledge, organizational capabilities; incentives; and organizational culture, strategy, and structure; and external environmental factors including institutional pressures, environmental dynamism and competitiveness and learning collaboratives. Lastly learning in the context of quality and safety improvement requires leadership that reinforces learning through actions and behaviors that affect people, such as coaching and trust building, and through influencing contextual factors, including providing resources, developing culture, and taking strategic actions that support improvement. Our review highlights the importance of leadership in both promoting a supportive learning environment and implementing learning processes. Keyword: collective learning, systematic review, scoping review, health care quality, patient safety, quality improvement